PAJAK KEBISINGAN DI INDONESIA : IMPLEMENTASI DAN POTENSI PENERIMAAN NEGARA (STUDI KASUS BANDARA SOEKARNO-HATTA) - Ilmi, Ghozi; Azizah , Faridah (Fakultas Ekonomi dan Bisnis Universitas Pasundan, 2024)
Anything causing negative externalities should ideally incur compensation for the losses suffered by others, commonly known as Pigovian tax, as in the case of noise pollution. Noise pollution refers to any unwanted sounds causing discomfort and negative impacts on the health and safety of those exposed to it. Airports are among the main sources of noise pollution due to aircraft operations exceeding reasonable noise thresholds. The negative impacts of noise pollution, particularly on residents within the airport noise radius, should be compensated through a tax scheme, often referred to as airport noise tax. Many developed countries have implemented compensation about aircraft noise through taxes. This study aims to explore the feasibility and potential of implementing a noise pollution tax in Indonesia. The research employs a qualitative descriptive method with data collected through documentation, including the Environmental Impact Analysis of Soekarno-Hatta Cengkareng Airport in 2017 and previous studies. Using descriptive analysis, collected data is elucidated to provide clarity on the phenomenon of noise pollution tax compensation. In this study, tax calculation is based on quantifying aircraft noise, which is then correlated with the value of residential properties assessed using the hedonic pricing model to determine the tax payable for each aircraft's noise emissions. The study concludes that implementing a noise tax at airports holds significant revenue potential for the government, intended to compensate noise-affected areas, and could be implemented across airports throughout Indonesia.